2023
DOI: 10.3390/mi14020410
|View full text |Cite
|
Sign up to set email alerts
|

RC Bridge Oscillation Memristor Chaotic Circuit for Electrical and Electronic Technology Extended Simulation Experiment

Abstract: The fourth basic circuit component, the memristor, has been proposed for a long time, but it is not mentioned in the experiment teaching system of Electrical and Electronic Technology. In this paper, an RC bridge oscillation chaotic circuit based on memristor is designed to solve this problem. The dynamical behavior of the circuit system is analyzed using Lyapunov exponents spectrum, bifurcation diagram, phase portrait and Poincaré map. A series of complex dynamical behaviors such as symmetric single-scroll co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An oscillator circuit via connecting a nonvolatile locally active memristor to other components was constructed by Li and complex phenomena such as multivolume attractors and symmetric coexisting attractors was discovered [18]. The RC bridge oscillation chaotic circuit based on the flux-controlled memristor was designed and the dynamical analyses showed that there are many different types of attractors coexisting in the system [19]. A multi-segmented memristor was introduced by Zhang into the Sprott-B system to construct several chaotic systems and revealed chaotic bursts and chaotic transients [20].…”
Section: Introductionmentioning
confidence: 99%
“…An oscillator circuit via connecting a nonvolatile locally active memristor to other components was constructed by Li and complex phenomena such as multivolume attractors and symmetric coexisting attractors was discovered [18]. The RC bridge oscillation chaotic circuit based on the flux-controlled memristor was designed and the dynamical analyses showed that there are many different types of attractors coexisting in the system [19]. A multi-segmented memristor was introduced by Zhang into the Sprott-B system to construct several chaotic systems and revealed chaotic bursts and chaotic transients [20].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the three fundamental circuit components, resistors, capacitors, and inductors, memristors possess unique memory resistance functional characteristics. Due to this distinctive memory property, memristors can find applications in various fields, including intelligent computing [2,3], neural networks [4][5][6], data mining [7], memory devices [8][9][10], and chaotic circuits [11][12][13], among others. However, because memristors have not been physically realized in the real world, research on memristors and memristor circuits has not attracted the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not until 2008 that HP Labs made a solid-state memristor, [8] which marks that the research on memristors has officially changed from theory to practice. With the deepening of the research on memristors, [9,10] the special nonlinearity and nonvolatility of memristors have made them widely used in chaos, [11][12][13] neural networks, [14][15][16][17][18][19][20] secure communication, [21,22] memory, [23] neurons, [24] and chaotic oscillators. [25,26] More and more researchers have found that adding memristors to chaotic circuits will greatly increase the complexity of the system and cause some other behaviors in the chaotic system.…”
Section: Introductionmentioning
confidence: 99%